The political and institutional basis of Korea's skill formation system - Park, Sang-Young [Verfasser] (My University, 2013)
"Korea's developmental skill formation system was shaped in the 1970s by the Korean developmental state that proactively sought rapid Heavy and Chemical Industrialisation as the nation's overarching goal. Vocational education at the upper secondary level and post-school in-company training in particular were strategically nurtured and closely managed by the state to supply the skilled workforce necessary, engendering a skill formation system subject to the state's policies. The state's tight control of the skill formation system was largely loosened in the 1980s, but since the 1990s it began to transform into a 'post-developmental' skill formation system geared toward Korea's increasingly knowledge-based and globalising economy. Although it is still in the making, the post-developmental skill formation system is significantly different from the previous system in that the focus has shifted to vocational education at the secondary and the tertiary levels, whereas in-company vocational training is being gradually marginalised. Furthermore, the post-developmental skill formation system in Korea is both state-led and market-based, reflecting fundamental and dynamic changes in the nature of the Korean state since the 1990s." (Authors' abstract, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 2.3 Berufsbildungspolitik; T 1.2 Historische Berufsbildungsforschung; I 2.3.4 Asien; Berufsbildungssystem; Schulische Berufsausbildung; Betriebliche Berufsausbildung; Berufsbildungspolitik; Bildungssteuerung; Politisches System; Historische Entwicklung; Südkorea; 1950-2010